A Study of Permissioned Blockchain-Based Framework for Land Ownership Tracking in Indonesia - Herny Christine; Koo Tito Novelianto; Meta Restiawati; Happrila Yuliana Jayanti; Afriyadi Afriyadi (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2022)
The rapid development of the economy in Indonesia has made land an important asset. The land registry system in Indonesia or known as Pendaftaran Tanah Sistematik Lengkap (PTSL) is enforced by the government to govern land property ownership management. However, the current land registry uses a conventional information system which lacks the ability to track data changes and verify their integrity, especially in land ownership documents. Introduction of unintended or fraudulent changes to the data may be made to look natural. This could be identified from the possibility of unauthorized users tampering and modifying the data in the land ownership document. Usually, they modify the data in land ownership documents mainly for their own personal gains or some might even attempt to monopolize the land transactions market or conduct illegal acts such as corruption. This prolonged issue could further lead to land disputes and uncertainty in land ownership issues. Therefore, this paper aims to propose a proof-of-authority permissioned blockchain concept to digitize and track land ownership registration. By utilizing blockchain technology, all of the records will be validated and stored securely in the blockchain network. In addition, permissioned access is added to only allow authorized users able to access the system; thus only specific users are able to perform actions on the system and are required to identify themselves. Through this proposed solution, the integrity of changes in land ownership documents can be achieved and validated.